Differential expression of immunoregulatory cytokines in adipose tissue and liver in response to high fat and high sugar diets in female mice - Weiner, Juliane; Dommel, Sebastian; Gebhardt, Claudia; Hanschkow, Martha; Popkova, Yulia; Krause, Kerstin; Klöting, Nora; Blüher, Matthias; Schiller, Jürgen; Heiker, John T. (Frontiers in Nutrition, 2023)
A comprehensive understanding of how the dietary components impact immunoregulatory gene expression in adipose tissue (AT) and liver, and their respective contributions to metabolic health in mice, remains limited.The current study aimed to investigate the metabolic consequences of a high-sucrose diet (HSD) and a high-fat diet (HFD) in female mice with a focus on differential lipid-and sucrose-induced changes in immunoregulatory gene expression in AT and liver. Female C57BL/6J mice were fed a purified and macronutrient matched high fat, high sugar, or control diets for 12 weeks. Mice were extensively phenotyped, including glucose and insulin tolerance tests, adipose and liver gene and protein expression analysis by qPCR and Western blot, tissue lipid analyses, as well as histological analyses of AT and liver.Compared to the control diet, HSD-and HFD-fed mice had significantly higher body weights, with pronounced obesity along with glucose intolerance and insulin resistance only in HFD-fed mice.HSD-fed mice exhibited an intermediate phenotype, with mild metabolic deterioration at the end of the study. AT lipid composition was significantly altered by both diets, and inflammatory gene expression was only significantly induced in HFD-fed mice. In the liver however, histological analysis revealed that both HSD-and HFD-fed mice had pronounced ectopic lipid deposition indicating hepatic steatosis, but more pronounced in HSD-fed mice. This was in line with significant induction of pro-inflammatory gene expression specifically in livers of HSD-fed mice.Overall, our findings suggest that HFD consumption in female mice induces more profound inflammation in AT with pronounced deterioration of metabolic health, whereas HSD induced more pronounced hepatic steatosis and inflammation without yet affecting glucose metabolism.